Reliable transmission control protocol for spatial information networks - ZHANG Min1; LUO Guang-chun1; WANG Jun-feng2; HUANG Lei3 (Tongxin xuebao)
A TCP-compatible reliable transmission protocol for spatial information networks SIN（i.e.,STP） was pro-posed.Compared with TCP,STP improves the transmission capability via enhanced algorithms of slow start,congestion avoidance,fast retransmission and recovery.Experiments validate the considerable performance improvements of STP against TCP and prove its adaptability in SIN.